Influence of helium ions beams with energies 0.12 MeV on sputtering process on surface of tungsten - Manuilenko, O.V.; Prokhorenko, E.M.; Pavlii, K.V.; Zajtsev, B.V.; Dubniuk, S.N.; Lytvynenko, V.V.; Kasatkin, Yu.A.; Prokhorenko, T.G. (Problems of Atomic Science and Technology, 2023)
The samples of tungsten with a purity of 99.5 and 99.7% were irradiated with helium ion beams (EHe⁺ = 0.12 MeV). The total sputtering coefficients for the sample depth up to 60 Å from the surface of sample were obtained. It was found that on the surface of tungsten, the number of pits (the flecking effect) significantly exceeds the number of bubbles (the blistering effect). The damage profiles of the surface of tungsten as a result of irradiation with helium ions are calculated. The areas of maximal display of effects of damage are determined.